2017
DOI: 10.1108/ijpcc-02-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Heavyweight extension to the UML class diagram metamodel for modeling context aware systems in ubiquitous computing

Abstract: Purpose The development of context-aware applications in ubiquitous environments depends not only on the user interactions but also on several context parameters. The handling of these parameters is a fundamental problem in these systems. The key purpose of this work is to enrich the unified modeling language (UML) class diagram with new constructs to provide a universal model capable of coping with the context-awareness concerns. Design/methodology/approach The authors provide a review of existing context h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Additionally, UML is used as a tool to design and model contexts. This has been reported in different implementation cases and exposed in a wide variety of related works [13,[44][45][46][47][48][49][50][51][52].…”
Section: Testing Ideas Through Experimentationmentioning
confidence: 99%
“…Additionally, UML is used as a tool to design and model contexts. This has been reported in different implementation cases and exposed in a wide variety of related works [13,[44][45][46][47][48][49][50][51][52].…”
Section: Testing Ideas Through Experimentationmentioning
confidence: 99%
“…Dzidek et al [23] showed that using and updating UML designs during the maintenance and evolution of a software system increased the functional correctness and design quality of the evolved system. The systematic literature review of da Silva et al [64] showed that the UML profile-based mechanism is often used to customize a class diagram to properly support the design of context-awareness and self-adaptiveness properties of self-adaptive systems [1,7,10,36,39,56,62,65,66]. Vathsavayi et al [34] use genetic algorithms to dynamically insert and remove design solutions from the application class diagram in response to the changing environment, and propagate the design-level changes to the code level using the Javaleon platform [29].…”
Section: Introductionmentioning
confidence: 99%